APPROPRIATE USAGE OF ANTIBIOTICS AND ITS COST-EFFECTIVENESS - Ivana Shafira Putri; Rebriarina Hapsari; V. Rizke Ciptaningtyas (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: Inappropriate use of antibiotics not only cause resistance, but also indirectly increase morbidity, mortality, and prolong the length of stay, which can lead to increased health care costs. Pneumonia is one of the infectious diseases with a high prevalence in Indonesia. It requires various antibiotic treatment that makes the antibiotic selection need to be considered in both clinical terms and cost-effectiveness. Aim: This study aimed to determine the association between the quality of antibiotic and cost-effectiveness in hospitalized pneumonia patients at Diponegoro National Hospital Semarang in the period 2015 - 2019. Methods: A cross-sectional study was performed in fifteen patients with community-acquired pneumonia (CAP). The medical records as samples were retrospectively obtained by total sampling method. The categories of antibiotic quality (appropriate and inappropriate) were determined according to the Gyssens criteria and analyzed using a cost-effectiveness table. The outcome measure was length of stay (LOS). Results : Mean LOS, mean antibiotic cost, and median total direct hospital cost of appropriate and inappropriate antibiotic quality respectively 3,27 days versus 6 days (p = 0.275), 123,302 IDR versus 286,000 IDR (p = 0.020), and 3,317,100 IDR versus 3,878,600 IDR (p = 0,602). Based on the cost-effectiveness table, the position of appropriate antibiotic quality was in column G (dominant), while the position of inappropriate antibiotic quality was in column C (dominated). Conclusions: The appropriate usage of antibiotics was more cost-effective than inappropriate. There was a significant differences of LOS between both categories.